PENGARUH MEDIA PEMBELAJARAN SWISH MAX TERHADAP HASIL BELAJAR PENGETAHUAN BAHAN MAKANAN SISWA SMK SWASTA ARINA SIDIKALANG - Sulistiawikarsih, Sulistiawikarsih; Liana Siburian, Romasta Nova (JURNAL KELUARGA SEHAT SEJAHTERA, 2020)
ABSTRACTThis study aims to determine: (1) Student learning outcomes in the Foodstuff Knowledge lesson using Swish Max learning media; (2) Student learning outcomes in Foodstuff Knowledge lessons that do not use Swish Max learning media; (3) The effect of using Swish Max learning media on student learning outcomes in Foodstuff Knowledge lessons. Data analysis techniques used data descriptions, trend test, normality test using the chi square formula, homogeneity test, and hypothesis testing. The results showed that the learning outcomes of students using Swish Max learning media in the Foodstuff Knowledge lesson based on the level of tendency were categorized as high at 56.67 percent and learning outcomes that did not use Swish Max learning media in the Foodstuff Knowledge lesson based on the level of tendency were included in the category. tends to be sufficient at 60.00 percent. Keywords: Media, Swish Max  ABSTRAKPenelitian ini bertujuan untuk mengetahui: (1) Hasil belajar siswa pada pelajaran Pengetahuan Bahan Makanan yang menggunakan media pembelajaran Swish Max; (2) Hasil belajar siswa pada pelajaran Pengetahuan Bahan Makanan yang tidak menggunakan media pembelajaran Swish Max; (3) Pengaruh penggunaan media pembelajaran Swish Max terhadap hasil belajar siswa pada pelajaran Pengetahuan Bahan Makanan. Teknik analisis data menggunakan deskripsi data, uji kecenderungan, uji normalitas menggunakan rumus chi kuadrat, uji homogenitas, dan uji hipotesis. Hasil penelitian menunjukkan bahwa hasil belajar siswa yang menggunakan media pembelajaran Swish Max pada pelajaran Pengetahuan Bahan Makanan berdasarkan tingkat kecenderungan termasuk kategori cenderung tinggi sebesar 56,67 persen dan hasil belajar yang tidak menggunakan media pembelajaran Swish Max pada pelajaran Pengetahuan Bahan Makanan berdasarkan tingkat kecenderungan termasuk kategori cenderung cukup sebesar 60,00 persen. Kata Kunci: Media, Swish Max